Pengaruh Profitabilitas, Keputusan Investasi, Kebijakan Deviden Dan Leverage Terhadap Nilai Perusahaan Pada Perusahaan LQ45 - Riska Dwi Handayani, Kadek; Werastuti, Desak Nyoman Sri (Universitas Pendidikan Ganesha, 2024)
The purpose of this study was to examine the effect of profitability, investment decisions, dividend policy, and leverage on firm value. This research is a type of quantitative research. The type of data used is secondary data obtained from www.idx.co.id and the company's website. The population in this study are companies listed on the LQ45 index on the Indonesia Stock Exchange (IDX) during the 2016-2020 period. The sample in this study was determined using the purposive sampling method. The total data used is 80. This test is carried out with multiple linear regression analysisThe results of this study indicate that profitability, investment decisions, dividend policy, and leverage have a positive effect on firm value.